The growth and survival rate of red tailed tinfoil, Barbonymus balleroides (Valenciennes, 1842) post-larvae in aquariums with different densities - Irin Iriana Kusmini; Fera Permata Putri; Deni Radona (Jurnal Iktiologi Indonesia, 2017)
Tinfoil barb Barbonymus balleroides (Valenciennes, 1842) is one of the local freshwater fish that have the potential to be cultured as fish consumption as well as ornamental fish. This study aimed to determine of the growth and survival rate of red tailed tinfoil post-larvae based stocking density (3 individual L-1, 4 individua lL-1 and 5 individual L-1). This study was conducted in plasma nutfah research station, Bogor and experimentally used completely randomized design (CRD) with three treatments and three replications for each treatment. The post-larvae used in the experiment were sized 0.37 cm from induced breeding spawning. The post-larvae were reared in the aquarium (dimension= 60x30x30 cm) with a volume of 34 liters water. During reared (90 days) post-larvae were given commercial feed (protein content =40%) at-satiation with frequency of three times per day. The result showed the value of length, weight and the highest specific growth rate (P<0.05) in the treatment of stocking density 5 individual^1 with value of 1.8 cm, 0.24 g and 2.72%, while the highest survival rate of 3 individual-1 with a value of 86.76%. Abstrak Ikan lalawak Barbonymus balleroides (Valenciennes, 1842) merupakan ikan lokal air tawar yang memiliki potensi untuk dibudidayakan sebagai ikan konsumsi maupun sebagai ikan hias. Tujuan penelitian ini untuk mengevaluasi pertumbuhan dan sintasan pascalarva ikan lalawak berdasarkan padat tebar (3 ekor L-1, 4 ekor L-1 dan 5 ekor L"1). Penelitian dilakukan di Instalasi Penelitian Plasma Nutfah Perikanan Air Tawar Cijeruk, Bogor dan dilaksanakan secara eksperimental menggunakan rancangan acak lengkap dengan tiga perlakuan dan tiga kali ulangan. Pascalarva yang digunakan berukuran 0,37 cm dan merupakan hasil pemijahan secara induksi hormon. Pemeliharaan dilakukan dalam akuarium berukuran 60x30x30 cm3 dengan volume air 34 L. Selama 90 hari pemeliharaan pascalarva diberi pakan komersial berbentuk remah yang mengandung protein 40 % secara at-satiasi dengan frekuensi tiga kali per hari (pagi, siang, dan sore). Hasil penelitian menunjukkan nilai panjang, bobot, dan laju pertumbuhan spesifik tertinggi (P<0,05) pada perlakuan padat tebar 5 ekor L-1 dengan nilai 1,8 cm, 0,24 g dan 2,72% sedangkan sintasan tertinggi pada perlakuan 3 ekor L-1 dengan nilai 86,76%.